Evidence-based governance in the electronic age : a World Bank / International Records Management Trust Partnership Project (Wolrd Bank Washington, D.C.US)
Reports on a five-year project that involves coordinating a global network of institutions and organisations to provide support for modernisng records management systems in parallel with measures to improve public sector management.
Keywords: RECORDS MANAGEMENT